Improving the framework for analyzing community resilience to understand rural revitalization pathways in China. (August 2022) - Zhang, Ruoyan; Yuan, Yuan; Li, Hongbo; Hu, Xiao
Abstract: Community resilience (CR) is receiving increasing attention within rural studies, especially as many rural communities, worldwide, appear to be gradually declining. In 2017, the Chinese government outlined a "rural revitalization strategy", which recommends four pathways for revitalizing rural communities and helping them to withstand external shocks. To advance understanding of rural revitalization pathways in China, we developed an improved conceptual framework for analyzing CR. The study's innovativeness lies in its integration of principles for building social-ecological resilience into the framework, and the provision of a step-by-step process for analyzing CR. We analyzed major risks and shocks faced within each of the four revitalization pathways in China on the basis of a literature review, and identified key slow variables and their mutual effects as well as corresponding thresholds and core indicators. Our results showed that slow-onset disturbances, which differ greatly among the four pathways, pose the greatest threat to CR. However, the impacts of slow variables on rural communities are often ignored as they are difficult to observe. Therefore, rules should be introduced to avoid shortsighted decisions in policymaking. Our findings can provide valuable inputs for the implementation of rural revitalization pathways in China. Moreover, they highlight the need for more empirical case studies focusing on diversified pathways. Highlights: We improved the conceptual framework for analyzing community resilience. Principles for building social-ecological resilience were integrated into the framework. A step-by-step process for analyzing community resilience was provided. Core indicators differed greatly among the four revitalization pathways in China. Impacts of slow-onset disturbances on rural communities are often ignored.